Nitrogen recovery from intensive livestock farms using a simplified ammonia stripping process - Finzi, Alberto; Ferrari, Omar; Riva, Elisabetta; Provolo, Giorgio (Frontiers in Sustainable Food Systems, 2024)
The ammonia (NH3) stripping process can recover nitrogen (N) from slurry and digestates as a mineral fertilizer, but it is currently expensive and difficult to manage at the farm level. Hence, simplification is required. This study aims to test a modular (on the basis of farm N surplus) slow-release NH3stripping process at a pilot plant scale. NH3 volatilization was promoted in a closed reactor and then the NH3 was removed by an air stream through the reactor headspace. The NH3-loaded air was purified in a scrubber, where NH3 reacted with sulfuric acid to form ammonium sulfate (AS). Eleven trials were conducted using pig slurry, dairy cattle slurry, and digestates. Seven trials were carried out with the reactors heated at 40°C, two trials at ambient temperature, and two trials with the addition of sodium hydroxide. To assess the technical–economic sustainability of the pilot plant, the total ammoniacal nitrogen (TAN) removal rate, electricity consumption, acid requirements, and AS quality and costs were evaluated. The pilot plant had TAN recovery amounts of 45% in 2 weeks with the reactors heated at 40°C, 64% in one week with NaOH addition, and 25% in 2 weeks at ambient temperature. The N concentration in the AS solution reached 85.9 g‧kg−1, with an average value of 35.2 g‧kg−1. The electricity consumption, acid requirement, and operational costs expected in an optimized system were approximately 0.52 kWh‧kgN−1 recovered, 3.5 kg pure acid‧kgN−1 recovered, and 0.86 €‧kgN−1 recovered, respectively. Compared to other technologies the simplified stripping process is slower but with similar removal efficiencies and lower energy consumption. Thus, this solution could be suitable to improve the N use in intensive livestock farms.